More sunlight exposure may improve the overall survival in patients with pancreas cancer - Melek Karakurt Eryılmaz; Hasan Mutlu; Şeyda Gündüz; Mükremin Uysal; Fatma Yaçın Müsri; Hasan Şenol Coşkun (Journal of Oncological Sciences, 2016)
The protective effect of sun exposure on prognosis of cancer and cancer risk was previously reported in some studies except for melanoma and skin cancer. In presented study we aimed to compare the effect of sunlight exposure on prognosis of patients with pancreatic cancer (PC) in two regions with different sunlight exposure. Totally of 139 patients with PC from Akdeniz University from Antalya (n:103) and Kocatepe University (n:36) from Afyon were analyzed retrospectively. Antalya and Afyon state have different sunlight exposure. Two groups were compared in terms of overall survival (OS). The median OS values were 10,9 [95% CI: 7,8–14,0] and 6,9 [95% CI: 3,9–9,9] months for Antalya and Afyon groups, respectively and it was found a significant difference between groups for OS (p = 0.015). Also, the region and stage were an independent prognostic factor. In conclusion, the patients with PC had better OS in the region with more sunlight exposure.